The Red Eye--More than meets the eye. - Lim, Lik Thai; Ting, Siew Leng (IJCRR, 2021)
The red eye is one of the most common eye presentations to health care centres. The red-eye can be divided into painless and painful. The painless red eye includes bacterial, viral, allergic conjunctivitis, dry eyes, episcleritis and subconjunctival haemorrhage. Meanwhile, the painful red eye can be more challenging, as some involve ophthalmic emergencies which are acute angle-closure attack, acute anterior uveitis, scleritis, orbital cellulitis, severe keratitis and severe thyroid eye disease (TED). Some red eye cases are simple and can be managed as an outpatient. Unresolved and complicated red-eye cases require ophthalmologist referral and further investigations on time. Painful red eye may be more than meets the eye, requiring referral to the ophthalmologists.